Difference of Chemical Bonds Between UDMA Bonding Agents with Ethanol Solvent and Acetone Solvent on Dentin Collagen - Nanik Zubaidah; Ruslan Effendy; Adioro Soetojo; Tri Estiyaningsih; Muhammad Iqbal Tanzil; Khusnul Khotimah (Association of Support to Oral Health Research (APESB), 2021)
Objective: To investigate the difference of chemical bonds between urethane dimethacrylate (UDMA) bonding agents with ethanol solvent and acetone solvent on dentin collagen. Material and Methods: This experimental comparison study used three groups: G1 (Control): UDMA and collagen; G2: UDMA, collagen and ethanol; and G3: UDMA, collagen and acetone. The groups were then pelleted and analysed with FTIR, then the peak value of carbonyl absorption band from each study group was calculated. The result of FTIR analysis and the peak of carbonyl absorption band (P) was calculated using the formula: P = (BC / AB) X 100; AB. BC is measured in centimeters. The study of chemical bond differences between ethanol-solvent UDMA agents compared with acetone-solvent on dentin collagen resulted in a graph of peak of carbonyl absorption bands of UDMA and dentin collagen groups. To determine the chemical bonds of UDMA from the top of the carbonyl ester absorption bands with wavenumber absorption in range 1700-1750 cm-1, the decreasing peak of the carbonyl absorption bands is assumed as more chemical bonds that formed. Data were analysed using Anova one way and Tukey HSD test. Results: There were significant differences between the three study groups (p<0.05). Conclusion: UDMA bonding agents' chemical bonds with acetone solvent are much higher than the chemical bonds between UDMA bonding agents with ethanol solvent on dentin collagen.